Normalized compression distance to measure cortico-muscular synchronization - Pascarella, Annalisa; Gianni, Eugenia; Abbondanza, Matteo; Armonaite, Karolina; Pitolli, Francesca; Bertoli, Massimo; L’Abbate, Teresa; Grifoni, Joy; Vitulano, Domenico; Bruni, Vittoria; Conti, Livio; Paulon, Luca; et al. (Frontiers in Neuroscience, 2022)
The neuronal functional connectivity is a complex and non-stationary phenomenon creating dynamic networks synchronization determining the brain states and needed to produce tasks. Here, as a measure that quantifies the synchronization between the neuronal electrical activity of two brain regions, we used the Normalized Compression Distance (NCD), which is the length of the compressed file constituted by the concatenated two signals, normalized by the length of the two compressed files including each single signal. To test the NCD sensitivity to physiological properties, we used NCD to measure the cortico-muscular synchronization, a well-known mechanism to control movements, in 15 healthy volunteers during a weak handgrip. Independently of NCD compressor (Huffman or Lempel Ziv), we found out that the resulting measure is sensitive to the dominant-non dominant asymmetry when novelty management is required (p=0.011; p=0.007 respectively) and depends on the level of novelty when moving the non-dominant hand (p=0.012; p=0.024). Showing lower synchronization levels for less dexterous networks, NCD seems to be a measure able to enrich the estimate of functional two-node connectivity within the neuronal networks that control the body.